INTEGRATED MATHEMATICAL MODEL OF THE CONTROL SYSTEM FOR UPPER-LIMB BIOPROSTHESIS BASED ON EMG AND PIEZOELECTRIC SIGNALS - KHVOSTIVSKYI, MYKOLA; KOVALYK, SERHII (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The article presents an integrated mathematical model of a control system for upper-limb bioprostheses that simultaneously incorporates electromyographic (EMG) signals as the user’s intention channel and piezoelectric signals as the sensory feedback channel. Existing approaches to prosthetic control, such as proportional EMG amplitude-based methods or pattern recognition of muscle activity, have well-known limitations including instability during long-term use, lack of smoothness in motion, sensitivity to electrode displacement, and difficulties in clinical implementation of computationally intensive deep learning solutions. In contrast, the proposed model formalizes both EMG and piezo signals through their envelopes, extracted using the Hilbert transform, which significantly reduces the influence of noise, high-frequency artifacts, and random fluctuations, while preserving the physiological meaning of the signals. This approach allows achieving smoother, more stable, and reliable prosthetic motion control.The system architecture integrates multiple modules: signal acquisition, preprocessing, envelope detection, control signal generation, DC motor actuation, and adaptive feedback. The EMG envelope reflects the integral level of muscle activation, providing direct representation of the user’s intended effort, while the piezo envelope reflects the average contact force, enabling real-time adjustment of grip strength. Such integration reproduces the natural bio-inspired principle of the human neuromuscular system, where central motor commands are continuously corrected by tactile and proprioceptive sensory feedback. The mathematical formulation of the model captures the dynamics of both the electrical and mechanical parts of the actuator, enabling the analysis of motor stability, energy efficiency, and response under varying load conditions.A closed-loop operational cycle is described, in which EMG serves as the driving input, whereas piezo feedback ensures adaptive regulation of force. If the grip is insufficient, the system automatically increases motor voltage; if excessive, it reduces actuation, thereby preventing object slippage, potential damage, or discomfort. The integrated model remains computationally efficient and can be readily implemented in MATLAB/Simulink environments for simulation, optimization, and clinical testing.The presented work demonstrates that combining intention-driven EMG input with environment-responsive piezoelectric feedback creates a synergistic and adaptive control mechanism. This bioinspired approach enhances prosthesis performance by increasing movement precision, smoothness, and safety, while reducing dependency on manual recalibration or complex algorithms. The findings provide a foundation for future development of adaptive and intelligent prosthetic control strategies tailored to user-specific muscle patterns and varying real-world conditions. Ultimately, the model contributes to bridging the gap between artificial and physiological motor functions, thus advancing the field of assistive biomedical technologies. У статті представлено інтегровану математичну модель системи керування біопротезом верхніх кінцівок, що поєднує канали наміру користувача (ЕМГ-сигнали) та сенсорного зворотного зв’язку (п’єзосигнали). Актуальність дослідження зумовлена необхідністю підвищення точності, плавності та адаптивності рухів біопротеза, що безпосередньо впливає на його функціональність та зручність використання. Запропонована модель враховує фізіологічні особливості м’язової активності та механічної взаємодії із зовнішніми об’єктами, відтворюючи логіку природної нервово-м’язової системи людини.ЕМГ-сигнали описано як стохастичний процес із подальшим виділенням огинаючої за допомогою Гільберт-перетворення, що дозволяє усунути високочастотні шуми та зберегти інформативність параметрів. П’єзосигнал, сформований у результаті п’єзоелектричного ефекту, використано для сенсорного контролю сили захвату; його огинаюча визначає інтегральний рівень тиску, що уможливлює стабілізацію хвату та запобігання вислизанню чи пошкодженню предметів. Інтеграція цих сигналів забезпечує баланс між наміром користувача та реакцією середовища, формуючи адаптивний зворотний зв’язок у замкненому контурі керування.У роботі також подано математичний опис електричної та механічної динаміки двигуна біопротеза, зокрема залежності сили захвату та швидкості руху кінцівки від параметрів струму та кутової швидкості ротора. Це дозволяє відтворити природні біомеханічні властивості, зокрема зниження швидкості при зростанні навантаження. Алгоритм функціонування системи описано у вигляді замкненого циклу, що включає етапи реєстрації сигналів, генерації керуючих впливів, виконання руху та сенсорної корекції.Запропонована модель створює основу для розробки адаптивних алгоритмів керування біопротезами, які можуть враховувати індивідуальні особливості користувачів та змінні умови експлуатації. Її практична реалізація у середовищі MATLAB/Simulink дозволяє проводити чисельні дослідження, оптимізацію та прогнозування роботи системи без потреби у великій кількості експериментів. Таким чином, результати дослідження відкривають перспективи підвищення функціональності біопротезів та наближення їх до фізіологічних аналогів.
Keywords: adaptive control; bioinspired system; EMG signal; mathematical modeling; piezo signal; sensory feedback; upper-limb prosthesis